Optimum display luminance under a wide range of ambient light for cockpit displays - Lin, Caixin; Yi, Xiangwei; Ji, Zhengxin; Hou, Dandan; Lin, Yandan (Optics express, 2022)
The self-luminous cockpit displays need to be adaptive to a wide range of ambient light levels, which changes from very low illuminance to very high levels. Yet, current studies on evaluation and luminance setting of displays in bright surroundings are still limited. In this study, a three-dimensional visual ergonomic experiment was carried out to investigate how bright a cockpit display should be to meet aircrew operational requirements under different illuminance. A lab study with a within-subjects (N = 12) design was conducted in a simulated cockpit. According to the Weber–Fechner’s Law, human observers evaluated five display luminance conditions (10 1 , 10 1.5 , 10 2 , 10 2.5 , 10 3 cd/m 2 ) under five ambient illuminance conditions (10°, 10 1 , 10 2 , 10 3 , 10 4 lx). Visual performance, visual fatigue and visual comfort were used as evaluation bases, which were measured by d2 task, subjective fatigue questionnaire and visual perception semantic scales. Nonlinear function fitting was used to calculate the optimal luminance under a certain illuminance. Finally, curvilinear regression was used to analyze the illuminance and its corresponding optimal luminance. Based on Silverstein luminance power function, a luminance adjustment model with the form of power function was obtained. The proposed three-dimensional model fits the experimental data well and is consistent with the existing studies. It can be regarded as a supplement and optimization of the previous model under high ambient illuminance. This study can contribute not only to the pleasing luminance setting of panel displays in aircraft cockpits but also to other self-luminous devices, such as tablet devices, outdoor monitoring equipment and advertising screens.